ANALISIS USAHA KACANG SANGRAI DIKABUPATEN KLATEN - Wahyu Dwi Wulandari; Suprapti Supardi Supardi; Wiwit Rahayu (MEDIAGRO, 2008)
Wahyu Dwi Wulandari. 2006. Effort Analysis Of Kacang Sangrai Agroindustry In Klaten Regency. Agriculture Faculty Of Sebelas Maret University. Surakarta Kacang sangrai agroindustry is industry which process peanut become kacang sangrai. Kacang sangrai agroindustry which is there in Klaten Tengah District  laboured in two scale, that is small industrial scale kacang sangrai agroindustry and  home industrial scale kacang sangrai agroindustry. Each scale give different profit This Script is done pursuant to research which have been done  with a purpose to study and compare advantage, profitability, efficiency, and risk of effort between small industrial scale kacang saragra agro ndustry and home industry scale kacang sangrai agroindustry. Basic method this research used descriptive. Research done in Klaten Tengah  District because Klaten Tengah District represent the single kacang sangrai producer  area in Klaten Regency. Intake Responder done by taking all kacang sangrai entrepreneur. Data collected by primary and secondary. As for data collecting technique with observation, interview, and record-keeping Result of Research indicate that profit per accepted raw material kuintal small industrial scale kacang sangrai agroindustry ( Rp. 88.693,- ) bigger than home  industry scale  (  Rp. 63.368,-).  Small industrial scale kacang sangrai agroindustry profitability ( 9,24 %) bigger than home industry scale kacang sangrai agroindustry profitability ( 6,48%). Both the effort scale profit because profitability bigger than 0. Efficiency of effort small industrial scale kacang sangrai agroindustry (RlC = 1,09) and home industry scale kacang sangrai agroindustry (R /C = 1,06) please express  that both the effort scale not yet is efficient. Small industrial scale kacang sangra Agroindustry ( KV = 0,09) and home industry scale ( KV = 0,26) indicating that both the effort scale have low risk. For result of this research, writer took conclusion that the profit, profitability, and efficiency small industrial scale kacang sangrai agroindustri bigger than home industry scale, while risk of effort small industri scale kacang sangrai agroindustri lower than home industry scale Suggestion which can be submitted in this research is Packaging done by contract labour and home industry scale sangrai bean entrepreneur cooperate with society in product marketing